The The Implication of The Meaning of Utterances in Defamation Cases: A Forensic Linguistics Study - Haryanto, Haryanto; Arimi, Sailal (Universitas Negeri Semarang, 2022)
This study aims to identify the implication of the meaning of utterances in defamation cases. It was a qualitative study. The data source was the utterances of defamation cases in the results of the 2016-2021 Supreme Court decision in Indonesia. The data were collected through observation. The data were analyzed qualitatively by using distributional method. The validity of the research was accomplished through triangulation of theory, triangulation of source, and peer discussion. The result of this study has revealed that there are four types of meaning such as conceptual meaning, connotative, thematic, and affective meaning. Conceptual meaning has occurred to be the most dominant followed by connotative, thematic, and affective meaning. Furthermore, these meanings were realized through words that have negative connotations which cause the object in the utterance to feel accused or humiliated. Therefore, it has indicated as a defamation utterance according to Law Number 19 of 2016 with Amendment on the Law Number 11 of 2008 concerning Information and Electronic Transactions (Undang-Undang Nomor 19 Tahun 2016 Perubahan atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik/UU ITE). Keyword: defamation utterance, forensic linguistics, meaning, UU ITE